Poverty, schooling, and beginning teachers who make a difference: a case study from England - McIntyre, Joanna; Thomson, Pat (Springer, 2016)
Education policy makers in England have, over the last thirty years, radically changed schooling. The introduction of a national curriculum, national testing re-gimes, school inspections and school league tables has been at the heart of these changes as they constitute the basis for claims for and concerns about school and system improvement. The pre-service education of teachers has also been trans-formed during this period. Once dominated by time spent in higher education, teacher ‘training’ as it is known, now consists of diverse routes, all much more school-based. The latest policy shift to ‘teaching schools’ and the ‘school direct’ route intentionally makes universities even more marginal to teacher preparation.